2016
DOI: 10.1016/j.ejro.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

MRI features in 17 patients with l2 hydroxyglutaric aciduria

Abstract: l-2-Hydroxyglutaric (l-2-HG) aciduria is a rare inherited metabolic disease usually observed in children. Patients present a very slowly progressive deterioration with cerebellar ataxia, mild or severe mental retardation, and various other clinical signs including extrapyramidal and pyramidal symptoms, and seizures Goffette et al. [1]. This leukencephalopathy was first described in 1980 Duran et al. [2]. Brain magnetic resonance imaging (MRI) demonstrates nonspecific subcortical white matter (WM) loss, cerebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
15
0
3
Order By: Relevance
“…The main imaging features of the cases with chronic clinical course in our series are consistent with that of previous literature. [3,21,22]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main imaging features of the cases with chronic clinical course in our series are consistent with that of previous literature. [3,21,22]…”
Section: Discussionmentioning
confidence: 99%
“…This could have contributed to the peripheral rim sign described along the striatum in previous reports. [4,21]…”
Section: Discussionmentioning
confidence: 99%
“…Brain MRI findings are quite specific in terms of L2HGA disease and enable making a diagnosis as a result of imaging obtained because of different symptoms. In a study conducted with 17 subjects, frontotemporal white matter involvement was reported in all subjects; parietal white matter involvement was found in 94% subjects and occipital white matter involvement was found in 88% ( 6 ). When the extension of white matter involvement was examined, it was observed that subcortical involvement predominated (82.3%) and central and periventricular white matter involvement were found in 11.7% and 5.9% of the subjects, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In different case series, different rates of globus pallidus, putamen, and caudate nucleus involvement have been reported. In the advancing stages of the disease, cerebral and cerebellar atrophy may be added to the radiologic findings ( 5 , 6 ). The definite diagnosis is made by demonstrating increased L-2-hydroxyglutaric acid in body fluids and/or by molecular analysis of the L2HGDH gene ( 1 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…First reported in 1980, and with little over 100 documented cases worldwide, L2HGA is a rare inherited metabolic condition associated with progressive brain damage and elevated levels of L-2-hydroxylate [2]. Only in 2004 was it discovered that L2HGA arises from a mutation in the L2HDGH gene, which is inherited in an autosomal recessive fashion [3], [4].…”
Section: Discussionmentioning
confidence: 99%